Sunday

October 26, 2014

October 26, 2014

Posted by **Andres** on Tuesday, October 11, 2011 at 8:15am.

- Calc -
**Reiny**, Tuesday, October 11, 2011 at 8:44amif dy1/dx = 3y1

then y1 = ae^(3x) , where a is a constant, a≠ 0

(check: dy1/dx = 3a(e^(3x)) = 3y1 )

if dy2/dx = 8x + 5

then y2 = 4x^2 + 5x + c

the y-intercept of y1 is (0,a), but that is also the y-intercept of y2

so in y2:

a = 0 +0 + c

a = c

when x=2

y1 = a(e^6) , y2 = 16+10+c = c + 26

but a=c, so

a(e^6) = a+26

a(e^6) - a = 26

a(e^6 - 1) = 26

a = 26/(e^6 - 1) , which would be the y-intercept

**Answer this Question**

**Related Questions**

math, please somebody help me - Given the function f(x) = x4 , and suppose g(x) ...

math - Suppose you have a rational function that its denominator is (X-c) and ...

Calculus - Suppose you have a rational function that its denominator is (X-c) ...

College Algebra - 1.The graph of y = - 1/2 |x - 5| - 3 can be obtained from the ...

pre calc - The Identity Function The Squaring Function The Cubing Function The ...

Calculus - Suppose that p(x) is the density function for heights of American men...

Calculus - Suppose that p(x) is the density function for heights of American men...

Calc - Let f be the function given by f(x) = tan x and let g be the function ...

calculus - In the following problem, suppose f(x) is continuous (and ...

calc - suppose tanh(x)=y express as a function of y coth (x)?